2016
DOI: 10.1108/bfj-02-2016-0060
|View full text |Cite
|
Sign up to set email alerts
|

In search of a model explaining organic food purchase behavior

Abstract: Purpose The purpose of this paper is to explore the domain relevance of a comprehensive yet almost overlooked theoretical framework for studying organic food purchase behavior in a global context. This conceptual paper argues that there exists an apparently powerful model in health behavior domain that may readily be brought into organic food purchase behavior research. The paper argues for domain relevance and proposes that Montano and Kasprzyk’s integrated behavior model may readily be used in organic food b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 87 publications
(104 reference statements)
0
7
0
Order By: Relevance
“…Studies conducted in the health sector, for example, those done by [17,19], found that to ensure changes in patients' behaviours, it was essential to ensure there were no severe environmental constraints faced by the patients. These included transportation and limited clinic hours, particularly for patients who wished to do a mammogram.…”
Section: Environmental Constraintsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies conducted in the health sector, for example, those done by [17,19], found that to ensure changes in patients' behaviours, it was essential to ensure there were no severe environmental constraints faced by the patients. These included transportation and limited clinic hours, particularly for patients who wished to do a mammogram.…”
Section: Environmental Constraintsmentioning
confidence: 99%
“…Rahman and Noor [19] proposed that habit was one of the critical factors influencing purchase behaviour. This factor was also considered an essential determinant for repeating the intention to purchase.…”
Section: Habitmentioning
confidence: 99%
See 3 more Smart Citations